Association Between Self-Advocacy and Academic Performance of Higher Education Students with Disabilities: A Meta-Analysis - Rahajeng, Unita Werdi; Hendriani, Wiwin; Paramita, Pramesti Pradna (The Center for Disability Studies and Services Brawijaya University, 2023)
Self-advocacy is one of the personal factors essential for students with disabilities in college obtaining satisfactory achievements. This meta-analysis proves the strength of the relationship between self-advocacy and one of the success parameters of students with disabilities, namely academic achievement. It followed the guidelines from PRISMA. A literature search was conducted in four databases: Scopus, Web of Science, Psychnet, and Proquest, and 328 articles were obtained. Finally, six articles remained for further analysis. Based on the analysis using the DerSimonian and Laird (DL) estimator model, the estimated effect size was 0.29 (p<0.001; 95% CI=0.20 – 0.38). Although the results of the meta-analysis show a significant positive correlation between variables, there are things that need to be considered in terms of heterogeneity and the risk of publication bias.